Quantitative Validation of a Teacher Performance Measurement Model in Mathematics: Implications for Instructional Quality - Ichdar Domu; Rosauli N. Samosir; Navel Oktaviandy Mangelep (International Journal of Educational Research, 2025)
This study aimed to develop a competency-based performance evaluation model for mathematics teachers at the junior secondary level. Recognizing the crucial role of teacher quality in student achievement, the study focused on measurable aspects of performance, including content mastery, instructional management, and professional commitment. A quantitative approach was employed using a research and development (R&D) framework, supported by a quasi-experimental design with pretest-posttest control groups. Data were collected via structured questionnaires, classroom observations, interviews, and expert validations through focus group discussions. Statistical analyses included descriptive statistics, ANOVA, t-tests, and confirmatory factor analysis using SPSS and LISREL. The results indicated that the developed model effectively differentiated teacher performance across various school categories, with 45% categorized as good, 53% adequate, and 2% poor. Student achievement was positively correlated, with 82% achieving the minimum competency threshold. The factor analysis confirmed a valid measurement model: F1 = 0.505ZX1 + 0.475ZX2 + 0.308ZX3, explaining 57.92% of the variance in teacher performance. The findings suggest that teacher evaluation must integrate multidimensional competencies and contextual factors to be accurate and actionable. This study contributes a validated, data-driven evaluation framework aligned with national standards and global educational expectations, offering practical implications for policy, supervision, and teacher development.